Optimasi Keuntungan Pertanian Melalui Program Linear: Studi Kasus pada Pertanian Padi dan Jagung - Cahyani, Ade Indah; Meida, Inka Nurul; Hasanah, Iswatun; Alfian, Muhammad Rijal; Maharani, Andika Ellena Saufika Hakim (Program Studi Matematika, 2025)
Indonesia is an agrarian country with great potential in the agricultural sector, particularly in key commodities such as rice and corn, which play an important role in food security and animal feed. However, limited resources such as land, fertilizer, and labor pose challenges in achieving production efficiency and maximum profits. This study aims to optimize agricultural land allocation to maximize profits using a linear programming model. The case study was conducted on agricultural land owned by a resident of Bajo Village, Bima Regency, West Nusa Tenggara. Primary data was collected through direct interviews, including land area, input requirements (fertilizer, pesticides, herbicides, and labor), and profit per hectare. The model was solved using the graphical method with the assistance of POM-QM for Windows and Google Colab application. The analysis results indicate that the optimal land allocation is 3.65 hectares for rice and 2.54 hectares for corn, yielding a maximum profit of Rp58.906.350,00. This solution meets all available resource constraints. These findings indicate that the linear programming approach is effective in helping farmers make data-driven decisions to improve land and resource management efficiency. The application of this model also opens opportunities for the implementation of similar methods in other sustainable agricultural planning, particularly in the context of small-scale agriculture with limited resources.